Infection of Cryphonectria parasitica by CHV1 hypovirus - effects on pathogenesis- related peroxidases and hydrolases - Tayechi, Mohamed Yosri (2022)
The fungus Cryphonectria parasitica (Murrill) Barr. is the causal agent of Castanea sativa chestnut blight, a disease that causes important economic losses in chestnut orchards along all world. In hypovirulent strains of C. parasitica, the hypovirulence is due to the presence of a virus, the Cryphonectria hypovirus 1 (CHV1), that attenuates pathogenicity by reducing the sporulation, male fertility, and the enzymatic activity of pathogenesis-related enzymes. In the northeast region of Portugal, and in other regions of Europe affected by C. parasitica, the release of C. parasitica hypovirulent strains on chestnut blight affected trees of C. sativa, has been used in the field as a biological control. The objective of this work is to evaluate and compare the effect of hypovirulence by CHV1 on the activity of pathogenesis-related enzymes (hydrolases and peroxidases), in different isolates of C. parasitica. For this, several virulent and hypovirulent (donors and converted) isolates were grown in appropriate microbiological media, and some pathogenesis-related enzymes activity was qualitatively and quantitatively evaluated.